Historians and Ideologues. Essays in Honor of Donald R. Kelly. Ed. A.T. Grafton and J.H.M.Salmon, 2001 - Makiłła, Dariusz (Czasopismo Prawno-Historyczne, 2004)
Recenzja: Historians and Ideologues. Essays in Honor of Donald R. Kelly. Ed. A.T. Grafton and J.H.M.Salmon, Rochester 2001, University of Rochester Press, s. XI, 358.